PENINGKATAN KAPASITAS APARAT ADMINISTRASI NEGARA MELALUI PELATIHAN DAN PENDIDIKAN - Melyana R Pugu; Karman (Prosiding Seminar Nasional Indonesia, 2025)
Increasing the capacity of state administrative apparatus through training and education is an important eflort to strengthen the performance of government and public services. Well- designed training can improve the knowledge, skills, and professionalism of the apparatus, so that they are able to carry out their duties more eflectively and efficiently. However, the implementation of training and education programmes is often faced with various challenges, such as budget constraints, inflexible time, and gaps between training materials and field needs. To overcome these problems, a strategy is needed that involves regular training needs analysis, the use of e-learning technology, and programme evaluation through participant feedback. With good management and responsiveness to existing challenges, this capacity building programme is expected to produce competent administrative officers who are ready to face better public service tasks.